2009
DOI: 10.1097/eja.0b013e328328f552
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of physical and mental recovery status after elective liver resection

Abstract: The SF-36 indicates that liver resection surgery has a higher impact on physical health than on mental health. QoR-9 determines the feasible time course of recovery with a 1-week return to baseline. Preoperative impaired physical health might predict postoperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
1
7
1
Order By: Relevance
“…The postoperative MCS in our patients did not differ significantly from baseline and only 23.5% of the patients had a clinically relevant decrease of postoperative MCS scores. This complies with findings of earlier studies [ 16 , 38 , 39 ]. When measured before surgery and 30 days after surgery, no effects on mental health were apparent in our major surgery patients.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The postoperative MCS in our patients did not differ significantly from baseline and only 23.5% of the patients had a clinically relevant decrease of postoperative MCS scores. This complies with findings of earlier studies [ 16 , 38 , 39 ]. When measured before surgery and 30 days after surgery, no effects on mental health were apparent in our major surgery patients.…”
Section: Discussionsupporting
confidence: 93%
“…In a cohort of 76 patients, Aljabri and collaborators detected a statistically significant decrease in PCS (measured with SF-36) five weeks after open abdominal aortic surgery (N = 76) [ 14 ]. A statistically significant decrease of PCS at one month was also observed after gastric and colorectal surgery using the SF-12 [ 16 , 38 ] in cohorts of 151 and 223 patients, and a similar pattern was reported for 19 patients with liver resection surgery [ 39 ]. This statistically significant decrease of physical quality of life at one month may be related to an ongoing healing processes consecutive to an postoperative acute systemic inflammatory response syndrome after major surgery including the sickness behaviour [ 2 ], or to incomplete postoperative rehabilitation [ 40 ].…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Previous study showed a significant decrease of nine-item QoR scores at POD1, POD3 and POD5 compared with baseline in hepatectomy [27]. However, the difference of nine-item QoR scores=18 in the immediate postoperative period was not as evident in the current study.…”
Section: Discussioncontrasting
confidence: 85%
“…However, with no specific questionnaire existing for patients undergoing liver resection for benign liver tumors, an individual questionnaire was designed. In this context, elements from the Short Form 36, McGill Pain Score, and European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core [26,29,30] were used. The questionnaire consists of 44 questions composed of multi-item scales to evaluate physical role and emotional, cognitive, and social functioning.…”
Section: Quality Of Life Assessmentmentioning
confidence: 99%